OWNERSHIP RESPONSIBILITY AND TENANT RIGHTS FROM THE PERSPECTIVE OF CONSUMER PROTECTION LAWS AND ISLAMIC LAW: A Case Study in Gampong Batoh Banda Aceh, Indonesia - Arif Afrijal; Muhammad Yusuf (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2026)
Boarding houses, as a form of residential service business, have given rise to legal relationships between boarding house owners and tenants that fall within not only civil law but also consumer protection law and Islamic law. Boarding house tenants use residential services in exchange for payment, so, normatively, they can be positioned as consumers, while boarding house owners are positioned as business actors. This study aims to analyse the position of boarding house tenants as consumers, the practice of boarding house rental relationships in the field, and the liability of boarding house owners under Law Number 8 of 1999 concerning Consumer Protection, and from an Islamic law perspective. This study employs an empirical legal method and a sociological juridical approach, drawing on interviews and literature. The results show that, normatively, boarding house tenants have a strong legal basis for protection in both positive law and Islamic law. Still, in practice, this protection has not been optimally implemented due to imbalances in bargaining power, weak written agreements, and low legal awareness among the parties. The Consumer Protection Law and the principle of ijarah contract in Islamic law both emphasise the obligation of good faith and the responsibility of boarding house owners towards tenants’ losses. Therefore, it is necessary to strengthen regulations and internalise the value of justice to realise a boarding house rental practice that is substantively fair.